Kebijakan Kunci Manajemen Transportasi Kota Dalam Masa dan Pasca Reformasi - Harun al-Rasyid S Lubis; Muhamad Isnaeni (The Institute for Research and Community Services, Institut Teknologi Bandung, 1999)
When we were still enjoying economic growth, it was already not that easy to plan an investment policy in transport and to manage the urban transport system, because at that time we already had a big problem, i.e. lack of government budget for handling the large scale demand and complex national transportation problem. Private sector participation started to be widely offered at that time, and up to now the atmosphere is still being improved. Suddenly, we face an economic flu or 'crisis' that will remain so far the next couple of years. This paper tries to answer questions that will naturaly appear, such as what is going to be the basic policy for urban transport management? What would be the objective and how should the planning approach now be adapted? And also, what ar the main issues that have to be put in front and what would the strategy be? For sure, in the meantime the practice of development planning, which has been based on growth theory paradigm, will no longer be applicable. With this reality, the main activity of urban transport management should be in optimal management of the existing infrastructure and facilities. If there is to be a new investment for urban transport system development in the era of 'crisis', it will be highly competing with other important sectors, such as agriculture, health and small business sectors. Such investment, if any, should be examined comprehensively about its cost-effectiveness from the social welfare view point. Within the urban transport system, institutional reform either in structure or procedure is a must. Lists of reforms that have been raised even before the crisis are still most likely relevant. Therefore they have to be continued with further action. This paper also tries to list the necessary improvements in urban transport management system that have to be considered during and after the reform period.